Fibrate-modulated Expression of Fibrinogen, Plasminogen Activator Inhibitor-1 and Apolipoprotein A-I in Cultured Cynomolgus Monkey Hepatocytes - Kockx, M.; Princen, H. M. G.; Kooistra, T. (Thrombosis and Haemostasis, 1998)
Fibrates are used to lower plasma triglycerides and cholesterol levels in hyperlipidemic patients. In addition, fibrates have been found to alter the plasma concentrations of fibrinogen, plasminogen activator inhibitor-1 (PAI-1) and apolipoprotein A-I (apo A-I). We have investigated the in vitro effects of fibrates on fibrinogen, PAI-1 and apo A-I synthesis and the underlying regulatory mechanisms in primary monkey hepatocytes.We show that fibrates time- and dose-dependently increase fibrinogen and apo A-I expression and decrease PAI-1 expression in cultured cynomolgus monkey hepatocytes, the effects demonstrating different potency for different fibrates. After three consecutive periods of 24 h the most effective fibrate, ciprofibrate (at 1 mmol/l), increased fibrinogen and apo A-I synthesis to 356% and 322% of control levels, respectively. Maximum inhibition of PAI-1 synthesis was about 50% of control levels and was reached by 1 mmol/l gemfibrozil or ciprofibrate after 48 h. A ligand for the retinoid-X-receptor (RXR), 9-cis retinoic acid, and specific activators of the peroxisome proliferator-activated receptor-α (PPARα), Wy14,643 and ETYA, influenced fibrinogen, PAI-1 and apo A-I expression in a similar fashion, suggesting a role for the PPARα/RXRα heterodimer in the regulation of these genes. When comparing the effects of the various compounds on PPARα trans-activation activity as determined in a PPARα-sensitive reporter gene system and the ability of the compounds to affect fibrinogen, PAI-1 and apo A-I antigen production, a good correlation (r = 0.80; p <0.01) between PPARα transactivation and fibrinogen expression was found. Apo A-I expression correlated only weakly with PPARα transactivation activity (r = 0.47; p = 0.24), whereas such a correlation was absent for PAI-1 (r = 0.03; p = 0.95). These results strongly suggest an involvement of PPARα in the regulation of fibrinogen gene expression.